PENERAPAN MEDIA KINCIR AIR SEDERHANA TERHADAP HASIL BELAJAR IPAS PESERTA DIDIK KELAS VI SDN NO. 228 TUNRENG TELLUE - Mar’atus Shalihah; Nurlina; Nurfadilah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the learning outcomes of students before and after the application of a simple water wheel media and to analyze the improvement in learning outcomes in the Natural and Social Sciences (IPAS) subject of grade VI of SDN No. 228 Tunreng Tellue. The background of this study is based on the low learning outcomes of students caused by conventional learning and the lack of use of interesting learning media. Therefore, learning innovations are needed that can increase student engagement and understanding. The type of research used is a pre-experiment with a One Group Pretest-Posttest design. The research subjects were 16 students who were taken using a saturated sampling technique. The instruments used were learning outcome tests, observation sheets, and documentation. Data were analyzed using descriptive statistics to see the picture of learning outcomes and the N-Gain test to determine the improvement in student learning outcomes. The results showed that the average pretest score of 73.75 was in the medium category, which indicates that students' initial abilities were still not optimal. After the application of the simple water wheel media, the average posttest score increased to 88.62 and was in the high category. The N-Gain test results showed an average score of 0.58, which falls into the moderate category, indicating an improvement in learning outcomes after the implementation of the media. Furthermore, the distribution of scores showed an increase in the number of students in the high and very high categories, with no more students in the low and very low categories after implementation.